If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(1-x)-x=2(2-2x
We move all terms to the left:
3(1-x)-x-(2(2-2x)=0
We add all the numbers together, and all the variables
3(-1x+1)-x-(2(-2x+2)=0
We add all the numbers together, and all the variables
-1x+3(-1x+1)-(2(-2x+2)=0
We multiply parentheses
-1x-3x-(2(-2x+2)+3=0
We add all the numbers together, and all the variables
-4x-(2(-2x+2)+3=0
| 6(3s+5)=84 | | 5(2l+9)=55 | | 3(4x+7)=-3 | | 3/8c−2=3/2c−12 | | 2(15-3y)-3y=-6 | | (u-10)*7=49 | | (3x+11)(x-4)=0 | | 2(1-y)=-1(y=2) | | 700–35w =450+15w | | 16+2t=3/2+9 | | 8/6=(a+4)/(a-1) | | x-2÷4=2 | | 3=x=-7 | | 3(7n-5)=15n-63 | | 2.4+10-0.35x=0.25 | | X-1=2x-10 | | 2(x+5)=7x+8-5x+2 | | 3(a+9/12)=3(a+7/12) | | 5x=4x=5 | | 13-9x=7x-19 | | 120=(4x+3)8 | | 2(2–2x)=–3x | | 27=-5x+120 | | 4x^2+4×=0 | | x+x-72=478 | | 30x+12=6(5x+2 | | 6(5m-3)=72 | | 4.49x*x/4.49x+x=5700 | | 15+m=39 | | -(y2-2)=y2-5-y2 | | (2m-4)^2-4(2m-4)+3=0 | | 8^x=16 |